2019
DOI: 10.1515/nanoph-2019-0121
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional to unidirectional emission of fluorescence controlled by optical traveling wave antennas

Abstract: Tailoring the fluorescence emission of quantum emitters to a desired direction is a crucial issue to achieve high efficient photodetection and realize unique optoelectronic devices. In this study, the directional emission of quantum dots controlled by optical traveling wave antennas based on 1D silver nanowires (NWs) was investigated. Both leaky waves and surface waves on a single NW are utilized for fluorescence emission control, and we show that the coupled fluorescence transforms from bidirectional to unidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…33−35 Due to the local effect of plasmonic field and ultrasmall mode volume, plasmonic nanocavities can break the optical diffraction limit and reach a strong coupling regime with quantum emitters at room temperature. 36,37 In recent years, exploring the active control of strong coupling between plasmonic nanocavities and different types of emitters, such as quantum dots, 38 molecular excitons, 39 and transition metal dihalides (TMDs), 40,41 has become a significant research direction. At the single nanocavity level, room-temperature strong coupling between plasmon modes and emitters bring promising benefits for fundamental and applied physics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33−35 Due to the local effect of plasmonic field and ultrasmall mode volume, plasmonic nanocavities can break the optical diffraction limit and reach a strong coupling regime with quantum emitters at room temperature. 36,37 In recent years, exploring the active control of strong coupling between plasmonic nanocavities and different types of emitters, such as quantum dots, 38 molecular excitons, 39 and transition metal dihalides (TMDs), 40,41 has become a significant research direction. At the single nanocavity level, room-temperature strong coupling between plasmon modes and emitters bring promising benefits for fundamental and applied physics.…”
mentioning
confidence: 99%
“…The strong coupling regime can be realized when the energy exchange rate between the plasmon and the emitters overwhelms their respective dissipation rates. In this regime, the coherent energy exchange leads to two new hybridized states, which appear as the vacuum Rabi splitting and mode hybridization in frequency–domain spectra. Due to the local effect of plasmonic field and ultrasmall mode volume, plasmonic nanocavities can break the optical diffraction limit and reach a strong coupling regime with quantum emitters at room temperature. , In recent years, exploring the active control of strong coupling between plasmonic nanocavities and different types of emitters, such as quantum dots, molecular excitons, and transition metal dihalides (TMDs), , has become a significant research direction. At the single nanocavity level, room-temperature strong coupling between plasmon modes and emitters bring promising benefits for fundamental and applied physics. , More noteworthy, recent advances in plexcitonic chirality have achieved strong coupling between plasmonic nanocavities and chiral molecules. , Wu et al observed and fitted the mode splitting and anticrossing behavior of chiral plexcitons in CD measurements .…”
mentioning
confidence: 99%